Pengaruh Kedisiplinan, Motivasi dan Kompensasi Terhadap Prestasi kerja karyawan PT. Wesitan Konsultasi Pembangunan di Makassar - Mardiana Ibrahim; Muhtazib Muhtazib (Universitas 17 Agustus 1945 Semarang, 2022)
Research Objectives To determine the influence of discipline, motivation and compensation variables on employee work performance at PT. Wesitan Development Consultation in Makassar. To find out what variables are most dominant in employee work performance at PT. Wesitan Development Consultation in Makassar. The research method used is a quantitative research method. Simultaneously shows that discipline, motivation and compensation factors have a significant effect on employee work performance at PT. Wesitan Development Consultation in Makassar. Partially, discipline, motivation and compensation factors significantly influence employee work performance at PT. Wesitan Development Consultation in Makassar. Partially, compensation factors have a dominant influence on employee work performance, followed by discipline and motivation factors in community service.